2018
DOI: 10.1016/j.neuron.2018.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Regional Heterogeneity of D2-Receptor Signaling in the Dorsal Striatum and Nucleus Accumbens

Abstract: Dopamine input to the dorsal and ventral striatum originates from separate populations of midbrain neurons. Despite differences in afferent inputs and behavioral output, little is known about how dopamine release is encoded by dopamine receptors on medium spiny neurons (MSNs) across striatal subregions. Here we examined the activation of D2 receptors following the synaptic release of dopamine in the dorsal striatum (DStr) and nucleus accumbens (NAc) shell. We found that D2 receptor-mediated synaptic currents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 73 publications
12
63
0
Order By: Relevance
“…In this regard, a recent study unveiled that D2R from the AcbSh have a higher sensitivity for DA than those from the DS. This difference has been attributed to postsynaptic signaling molecules that differ between the two regions 35 . In support of this hypothesis, our study revealed significant differences in expression of genes encoding for postsynaptic molecules that belong to G protein signaling and RGS family, which could account for the region-dependent D2R sensitivity to DA.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recent study unveiled that D2R from the AcbSh have a higher sensitivity for DA than those from the DS. This difference has been attributed to postsynaptic signaling molecules that differ between the two regions 35 . In support of this hypothesis, our study revealed significant differences in expression of genes encoding for postsynaptic molecules that belong to G protein signaling and RGS family, which could account for the region-dependent D2R sensitivity to DA.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that differential signaling properties of GPCRs, to which DRD2 belongs, contribute to striatal heterogeneity. Distinct signaling properties in striatal domains can thereby shape physiological changes of the striatal circuit and ultimately result in different behavioral readouts (Marcott et al, ).…”
Section: Emerging Complexity Of Striatal Functionmentioning
confidence: 99%
“…The discovery of GPCR signalling through G protein–independent mechanisms, as well as preferential coupling to specific Gα subunits, has spurred new avenues of research that offer a more nuanced view of how D2 receptors may generate sub–cell‐type specificity to drive different responses to midbrain dopamine with distinct behavioural consequences . Using exogenous GIRK channels expressed in indirect D2‐MSNs in the NAc or dorsal striatum to obtain functional readouts of D2R activity, Marcott and colleagues revealed regional differences in how dopamine signals via D2 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular responses to dopamine in the NAc exhibited slower kinetics and less sensitivity to dopamine compared to D2‐MSNs in the dorsal striatum. These differences were driven by D2R preferential coupling to Gα o as opposed to Gα i subunits in the NAc . How regional D2R functional selectivity with respect to G proteins affects D2R‐dependent behaviours, including motivation, remains to be determined.…”
Section: Introductionmentioning
confidence: 99%